ability of fish oil to suppress tumor necrosis factor α production by peripheral blood mononuclear cells in healthy men is associated with polymorphisms in genes that influence tumor necrosis factor α production - Grimble, Robert F; Howell, W. Martin; O'Reilly, Gillian; Turner, Stephen J; Markovic, Olivera; Hirrell, Sharon; East, J. Malcolm; Calder, Philip C (The American journal of clinical nutrition, 2002)
Background: Tumor necrosis factor α (TNF-α) mediates inflammation. High TNF-α production has adverse effects during disease. Polymorphisms in the TNF-α and lymphotoxin α genes influence TNF-α production. Fish oil suppresses TNF-α production and has variable antiinflammatory effects on disease. Objective: We examined the relation between TNF-α and lymphotoxin α genotypes and the ability of dietary fish oil to suppress TNF-α production by peripheral blood mononuclear cells (PBMCs) in healthy men. Design: Polymorphisms in the TNF-α (TNF*1 and TNF*2) and lymphotoxin α (TNFB*1 and TNFB*2) genes were determined in 111 healthy young men. TNF-α production by endotoxin-stimulated PBMCs was measured before and 12 wk after dietary supplementation with fish oil (6 g/d). Results: Homozygosity for TNFB*2 was 2.5 times more frequent in the highest than in the lowest tertile of inherent TNF-α production. The percentage of subjects in whom fish oil suppressed TNF-α production was lowest (22%) in the lowest tertile and doubled with each ascending tertile. In the highest and lowest tertiles, mean TNF-α production decreased by 43% (P < 0.05) and increased by 160% (P < 0.05), respectively. In the lowest tertile of TNF-α production, only TNFB*1/TNFB*2 heterozygous subjects were responsive to the suppressive effect of fish oil. In the middle tertile, this genotype was 6 times more frequent than the other lymphotoxin α genotypes among responsive individuals. In the highest tertile, responsiveness to fish oil appeared unrelated to lymphotoxin α genotype. Conclusion: The ability of fish oil to decrease TNF-α production is influenced by inherent TNF-α production and by polymorphisms in the TNF-α and lymphotoxin α genes.